Fatigue Life Analysis of FSO Mooring Chain by Considering the Effects of Offloading Load - Hafizh Muhammad Naufal Shidqi; Nur Syahroni; Daniel Mohammad Rosyid; Dewinta Putri Cahyaningtyas (Institut Teknologi Sepuluh Nopember, 2023)
mooring chains are critical components in the maritime industry used to secure ships and floating oil and gas platforms such as FSOs to stay in their designated positions. The loads exerted on mooring chains during routine operations and additional loads during offloading operations can cause structural fatigue. Therefore, fatigue life analysis of mooring chains is essential to ensure safety and optimal performance. This study aims to conduct fatigue analysis of mooring chains by considering an important factor, namely the influence of offloading. Offloading load refers to the additional load exerted on the mooring chain during loading and unloading operations. The mooring system configuration uses a spread mooring system of 8 chains (4x2), 87 mm in diameter, with 20% pretension. In the fatigue analysis, the